PELANGGARAN MEREK TERKENAL MELALUI JUAL-BELI BARANG DI MEDIA JEJARING SOSIAL FACEBOOK - Ratna P, Ni Nyoman Nadia; Darmawan, Ni Ketut Supasti; Sudarsana, I Ketut Sandi (Kertha Semaya : Journal Ilmu Hukum, 2013)
Trademark infringement is widely known happened in trade using social mediafacebook, this is happened because the consumer want to have a branded goods with cheapprice, this make some people take advantages by providing them with fake goods of famousbrand goods and then sell it with cheap price. Development in technology and informationin the internet in particular the coming of facebook make this people easier to sell their fakegoods.
Keywords: infringement, famous brand, facebook, fake goods